2004
DOI: 10.1183/09031936.04.00117803
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord trace elements and minerals and risk of early childhood wheezing and eczema

Abstract: It has been suggested that foetal nutrition might influence the inception of wheezing and atopic disorders in childhood but specific nutrients have not been implicated.In the Avon Longitudinal Study of Parents and Children umbilical cord samples were assayed for trace elements and minerals, and mothers were asked about wheezing and eczema in their children. Associations of cord concentrations of selenium, zinc, copper, manganese, magnesium, iron, lead and mercury with wheezing at 30–42 months, with wheezing pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
112
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(128 citation statements)
references
References 41 publications
11
112
5
Order By: Relevance
“…Rather, we observed a potential unadjusted protective effect of maternal intake of dietary folate on the risk of eczema. In addition, we did not confirm the associations that have been reported between vitamin C (Litonjua et al, 2006), calcium (Miyake et al, 2010b) and iron (Shahen et al, 2004) and the risk of eczema. So far, no study has investigated the effect of maternal intake of antioxidants on the risk of rhinitis in the offspring.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Rather, we observed a potential unadjusted protective effect of maternal intake of dietary folate on the risk of eczema. In addition, we did not confirm the associations that have been reported between vitamin C (Litonjua et al, 2006), calcium (Miyake et al, 2010b) and iron (Shahen et al, 2004) and the risk of eczema. So far, no study has investigated the effect of maternal intake of antioxidants on the risk of rhinitis in the offspring.…”
Section: Discussioncontrasting
confidence: 55%
“…Some studies have reported a reduced risk of asthma and wheezing in the offspring with high maternal intake of vitamin E during pregnancy (Martindale et al, 2005;Devereux et al, 2006;Litonjua et al, 2006;Miyake et al, 2010a), whereas no association was observed regarding eczema (Devereux et al, 2006;Litonjua et al, 2006;Miyake et al, 2010b). Similar inconsistencies have been seen concerning maternal intake of zinc and the risk of allergic outcomes (Shahen et al, 2004;Martindale et al, 2005;Devereux et al, 2006;Litonjua et al, 2006;Miyake et al, 2010b). Umbilical cord selenium and iron has been associated with wheezing and eczema in children (Shahen et al, 2004).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…In animal models, vitamin E, zinc and vitamin D have been shown to modify fetal lung development, and vitamin E, zinc, vitamin D and PUFA can modulate T-cell responses. In humans, birth cohort studies have reported associations between wheezing and eczema in early life and low prenatal status of selenium and iron (17) , low maternal intake of vitamin E (9,18,19) , vitamin D (20,21) , apple and fish (10,22,23) .…”
Section: Maternal Diet During Pregnancymentioning
confidence: 99%
“…Moreover, exposure to specific nutrients and factors via breast milk is critical for development 62 . With regards to this, many factors have been characterised to be crucial in development such as exposure to pollutants, intake of folic acid, vitamin D, antioxidants such as selenium [63][64][65] , and most importantly FA (ref. 66,67 ).…”
Section: Fatty Acids In Maternal and Offspring Healthmentioning
confidence: 99%